Loss of p53 causes mitochondrial DNA depletion and altered mitochondrial reactive oxygen species homeostasis - Lebedeva, Maria A.; Eaton, Jana S.; Shadel, Gerald S. (Biochimica et biophysica acta, 2009)
In addition to its central role in cellular stress signaling, the tumor suppressor p53 modulates mitochondrial respiration through its nuclear transcription factor activity and localizes to mitochondria, where it enhances apoptosis and suppresses mitochondrial DNA (mtDNA) mutagenesis. Here we demonstrate a new conserved role for p53 in mtDNA copy number maintenance and mitochondrial reactive oxygen species (ROS) homeostasis. In mammals, mtDNA is present at thousands of copies per cell and is essential for normal development and cell function. We show that p53 null mouse and p53 knockdown human primary fibroblasts exhibit mtDNA depletion and decreased mitochondrial mass under normal culture growth conditions. This is accompanied by a reduction of the p53R2 subunit of ribonucleotide reductase mRNA and protein and of mitochondrial transcription factor A (mtTFA) at the protein level only. Finally, p53-depleted cells exhibit significant disruption of cellular ROS homeostasis, characterized by reduced mitochondrial and cellular superoxide levels and increased cellular hydrogen peroxide. Altogether, these results elucidate additional mitochondria-related functions for p53 and implicate mtDNA depletion and ROS alterations as potentially relevant to cellular transformation, cancer cell phenotypes, and the Warburg Effect.